APLIKASI FAULT TREE ANALYSIS PERBEDAAN PERSEPSI CAMPUS SUSTAINABILITY MAHASISWA DALAM PERILAKU PRO LINGKUNGAN DILINGKUNGAN KAMPUS - Annisa Amalia Utami; Susatyo N.W.P. (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
The concept of green campus directs the operation of universities as an environmentally-based educational institution which also has an important role for the environment of the future. In Semarang, there are 2 (two) state universities that are included in UI Green Metric program, namely Diponegoro University (UNDIP) and University of Semarang (UNNES). UNNES’ rank in 2014 UI Green Metric which is better than the UNDIP’s rank also indicates that students at UNNES have more perception about knowledge and high commitment to campus sustainability compared to students in UNDIP. There is a correlation between the knowledge and commitment of students to the vision of the campus in order to achieve campus sustainability, as well as there appears differences between knowledge and commitment to conduct pro-environment activities of both universities. To know the significance of difference perception about campus sustainability between students of UNDIP and UNNES, questionnaires to 165 student of UNDIP and 165 student of UNNES are disseminated. The result of the survey concludes that the perception of campus sustainability of UNDIP students is still under UNNES. To identify the root causes of the problem of low interest and knowledge of students to the campus sustainability in UNDIP, a tool of problem solving which is Root Cause Analysis (RCA) with Fault Tree Analysis technique is required.